Hereditary Hemorrhagic Telangiectasia - a literature review - Marcel Stodolak; Aleksandra Krużel; Kamil Kłos; Piotr Sajdak; Justyna Tomasik; Marika Dębik; Łukasz Szydłowski; Klaudia Żurowska; Seweryn Ziajor; Artur Bednarski; Mikołaj Turski (Journal of Education, Health and Sport, 2024)
Introduction and purpose: Hereditary hemorrhagic telangiectasia (HHT), also known as Osler-Weber-Rendu syndrome, is a rare and complex vascular disorder characterized by abnormal blood vessel formation. It can present significant challenges in diagnosis and management, as it is currently estimated up to 90% of those affected are never diagnosed. Despite its rarity, HHT can carry substantial implications for patients and their families, at times requiring comprehensive medical care and support. This paper aims to provide an in-depth exploration of HHT, encompassing its epidemiology, genetics, clinical manifestations, diagnostic approaches, and current management strategies. Moreover, we hope to point out possible areas in need of future research.